Multifunctional coating diaphragm for lithium metal battery and lithium metal battery
By using multifunctional coating technology on the separator of lithium metal batteries, a separator with high modulus, high strength, high heat resistance and high wettability is prepared, which solves the safety risks and electricity of lithium metal batteries in practical applications. The problem of poor chemical performance achieves longer cycle life and higher safety.
Patent Information
- Application Number
- CN202510019740.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In practical applications, lithium metal batteries are subject to the formation of lithium dendrites, parasitic reactions between lithium and electrolytes, and insufficient thermal stability and wettability of the separator, resulting in safety risks and poor electrochemical performance.
A multifunctional coated diaphragm, including a base diaphragm, an amide fiber coating and a metal compound coating, is prepared by electrospinning and electrostatic spraying technology to form a three-layer structured diaphragm.
It improves the modulus, strength, heat resistance and wettability of the diaphragm, enhances the safety and electrochemical properties of the battery, effectively resists lithium dendrites puncture, and extends the cycle life of the battery.
Smart Images

Figure CN119447708A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium metal batteries, and in particular to a multifunctional coated diaphragm for lithium metal batteries and a lithium metal battery. Background Art
[0002] As the electric vehicle market continues to grow, rechargeable lithium-ion batteries with graphite as the negative electrode cannot keep up with the demand for high energy density batteries. Therefore, it is urgent to develop rechargeable batteries with higher energy density to meet the growing demand, because lithium metal has a high theoretical capacity and low electrochemical redox potential, and has been considered as the ultimate negative electrode candidate for the next generation of rechargeable batteries. However, the practical application of lithium metal batteries is seriously troubled by a series of problems, mainly including the formation of harmful lithium dendrites and parasitic reactions between lithium and electrolytes; in particular, the growing lithium dendrites form "dead lithium" and "dendrites", which may penetrate the separator during the cycle, thus bringing certain safety risks.
[0003] In order to overcome the above shortcomings, workers have customized the chemical composition of SEI by using different solvents, optimizing lithium salt concentrations, adding electrolyte additives, etc., thereby improving the stability of lithium metal batteries. However, the solvents and additives in the electrolyte are usually very expensive and may be consumed and exhausted during the cycle. Alternatively, various three-dimensional porous skeletons are created to reduce the local current density and ensure sufficient lithium-philic sites, but porous skeletons are usually poorly scalable, which inevitably exposes a large surface area of the lithium metal anode, resulting in more serious side reactions between the lithium metal anode and the electrolyte.
[0004] In addition, the construction of an ideal artificial SEI with synergistic stabilization by coating the lithium surface with a protective layer composed of ceramics, polymers or their hybrids provides a promising approach for large-scale applications. However, due to the high reactivity of lithium, this method has high requirements for the operating environment, resulting in high manufacturing costs. Although the currently commercially available polyolefin separators such as polypropylene and polyethylene have the advantages of high mechanical strength and low cost, their shortcomings such as poor thermal stability and poor wettability with electrolytes have become key factors hindering their further application. Therefore, in order to improve the safety and electrochemical performance of lithium metal batteries, the use of a protective layer on the separator instead of introducing a protective layer on the surface of the lithium negative electrode can effectively circumvent the shortcomings of the above strategy. Summary of the invention
[0005] The purpose of the present application is to provide a multifunctional coated diaphragm for lithium metal batteries and a lithium metal battery. The diaphragm has a simple preparation process and is easy to mass produce. It is in contact with the metallic lithium negative electrode, which helps to construct a uniform and ultra-thin artificial SEI and has good electrochemical properties, providing a new idea for manufacturing a new multifunctional commercial diaphragm with a simple preparation method and scalable process.
[0006] The purpose of this application can be achieved through the following technical solutions: A multifunctional coated diaphragm for a lithium metal battery comprises a base diaphragm, a first coating layer and a second coating layer.
[0007] The first coating layer is disposed on the surface of the base diaphragm and is an amide fiber coating obtained by an electrospinning method; The second coating layer is arranged on the surface of the first coating layer and is a metal compound coating obtained by an electrostatic spraying method.
[0008] Preferably, the thickness of the basic membrane is 5-16 um, the thickness of the first coating layer is 3-5 um, and the thickness of the second coating layer is 3-5 μm.
[0009] Preferably, the base membrane is a microporous membrane, specifically one of a commercial PE membrane, a commercial PP membrane and a PE / PP composite membrane.
[0010] Preferably, the second coating layer is located on the side close to the metallic lithium negative electrode.
[0011] The method for preparing the multifunctional coated diaphragm for lithium metal battery comprises the following steps: The amide fiber, the binder, the conductive agent, the additive and the solvent are uniformly mixed to obtain a first coating slurry; uniformly mixing the metal compound, the binder and the solvent to obtain a second coating slurry; The first coating slurry is coated on the surface of the base diaphragm by electrostatic spinning, and a first coating layer is obtained after drying; the second coating slurry is coated on the side of the first coating layer away from the base diaphragm by electrostatic spraying, and a second coating layer is obtained after drying, thereby obtaining the multifunctional coated diaphragm for lithium metal batteries.
[0012] Preferably, the first coating slurry comprises the following raw materials in percentage by mass: 22-32% of amide fiber, 1-5% of binder, 0-1% of conductive agent, 0-2% of auxiliary agent, and 60-77% of solvent.
[0013] Preferably, the second coating slurry comprises the following raw materials in percentage by mass: 26% metal compound, 2% binder, and 72% solvent.
[0014] Preferably, the amide fiber comprises the following structure:
[0015] Among them, R 1 and R 2 Same or different, R 1 and R 2Each of them is independently selected from any one of hydrogen, alkane, alkene, halogenated hydrocarbon, methoxy, benzene ring, oxygen-containing benzene ring, acyl, halogenated acyl, benzoyl, amide, and halogen elements.
[0016] Preferably, the amide fiber is at least one of aramid fiber, polyamide fiber, polyesteramide fiber, polyimide fiber, polysulfoneamide fiber, polyaramid fiber, polynicotineamide fiber, polycarbonamide fiber, polyoxamide fiber, polyoxamide fiber, polyfuramide fiber, polyfluoroamide fiber, and polyphenylamide fiber.
[0017] More preferably, the amide fiber is aramid fiber.
[0018] Preferably, the metal compound is at least one of metal oxide, metal sulfide, metal selenide, metal phosphide, metal nitride and metal fluoride.
[0019] More preferably, the metal compound is a metal oxide.
[0020] Preferably, the binder is at least one of polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyacrylic acid, polyethylene oxide, sodium carboxymethyl cellulose, styrene butadiene rubber, hydroxypropyl methylcellulose, carboxy styrene butadiene latex and polyvinyl alcohol.
[0021] More preferably, the binder is polyvinylidene fluoride.
[0022] Preferably, the auxiliary agent is at least one of perfluoroalkyl ethoxymethyl ether, lithium polyacrylate, polyoxyethylene alkylamide, lithium chloride, fatty alcohol polyoxyethylene ether, sodium butylnaphthalene sulfonate, sodium isethionate, polyvinylidene fluoride-hexafluoropropylene, silicon dioxide, sodium dodecyl sulfonate, polyethylene oxide, polysiloxane, and carboxymethyl cellulose salt.
[0023] More preferably, the auxiliary agent is lithium chloride.
[0024] Preferably, the conductive agent is one or more of carbon black, conductive graphite, carbon fiber, carbon nanotube, and graphene.
[0025] More preferably, the conductive agent is graphene.
[0026] Preferably, the solvent is one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, potassium hydroxide solution, acetonitrile, ethanol, isopropanol, tert-butanol, ethylene glycol dimethyl ether, dimethyl sulfoxide, and deionized water.
[0027] Preferably, the electrospinning voltage is 22 kV, the distance between the roller and the needle is 10-20 cm, and the needle advancement speed is 0.2-1 mL / h.
[0028] Preferably, the electrostatic spray voltage is 10 kV, the spraying distance is 10-20 cm, and the needle advancement speed is 0.5-2 mL / min.
[0029] A lithium metal battery comprises a positive electrode, a negative electrode, a diaphragm and an electrolyte, wherein the diaphragm is the multifunctional coated diaphragm for the lithium metal battery.
[0030] Beneficial effects of the present invention: The present invention provides a multifunctional coated diaphragm for a lithium metal battery with a three-layer structure. A first coating layer and a second coating layer are respectively formed on the surface of a base diaphragm by electrostatic spinning and electrostatic spraying, wherein the first coating layer is an amide fiber coating, and the second coating layer is a metal compound coating. By introducing two coatings of different properties, the multifunctional coated diaphragm provided by the present invention ultimately has the characteristics of high modulus, high strength, high heat resistance, high wettability and the like. It not only adapts to complex processing environments, but also has excellent thermal stability to improve the safety of the battery, resist the piercing of lithium dendrites generated in the lithium metal battery, and effectively improve the cycle life of the lithium metal battery.
[0031] The high-performance amide fiber coating of the present invention is a key component of the battery separator layer. Its good ion conductivity helps the transmission of lithium ions in the battery, resists chemical corrosion of the electrolyte and active substances, and prolongs the service life of the battery.
[0032] The electrospinning process is used in the preparation of the amide fiber coating of the present invention. The electrospinning method is a new nanofiber preparation technology. The nanofiber membrane prepared by the electrospinning method has the characteristics of large specific surface area and high porosity, and can effectively improve the mechanical properties and thermal stability of the diaphragm.
[0033] The metal compound coating of the present invention can provide an electronic conductive channel, and the rapid migration of ions and electrons also makes it possible for high-power lithium batteries to be charged and discharged with high energy, safety and reliability; the micro / nano particles on the surface of the coating prepared by the electrostatic spraying method have good dispersion and high purity, and the diameter can reach the micro / nano scale. The spraying process is formed in one step, and no additional templates and post-processing steps are required. The operation is convenient and the thickness and uniformity of the surface coating can be effectively controlled.
[0034] The multifunctional coated diaphragm for lithium metal batteries provided by the present invention can not only effectively isolate the positive and negative electrodes of the battery, prevent short circuits and direct electrical contact, and ensure the safety of the battery, but also has a simple preparation process and is easy to mass produce; contact with the metallic lithium negative electrode helps to construct a uniform and ultra-thin artificial SEI, and has good electrochemical properties, providing a new idea for manufacturing a new multifunctional commercial diaphragm with a simple preparation method and scalable process. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] The present invention will be further described below in conjunction with the accompanying drawings.
[0036] Figure 1 It is a schematic structural diagram of a multifunctional coated diaphragm for a lithium metal battery of the present invention; Figure 2 It is a comparison diagram of the ionic conductivity and electrolyte contact angle of the diaphragms of Examples 1-5 of the present invention and Comparative Examples 4-8; In the figure: 1. basic diaphragm; 2. first coating layer; 3. second coating layer. DETAILED DESCRIPTION
[0037] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] A multifunctional coated separator for a lithium metal battery comprises a base separator 1, a first coating layer 2 and a second coating layer 3.
[0039] The first coating layer 2 is disposed on the surface of the base diaphragm 1 and is an amide fiber coating obtained by electrospinning; The second coating layer 3 is disposed on the surface of the first coating layer 2 and is a metal compound coating obtained by an electrostatic spraying method.
[0040] The second coating layer 3 is located on the side close to the metal lithium negative electrode.
[0041] The thickness of the basic diaphragm 1 is 5-16 um, the thickness of the first coating layer 2 is 3-5 um, and the thickness of the second coating layer 3 is 3-5 μm.
[0042] The basic diaphragm 1 is a microporous diaphragm, specifically one of a commercial PE diaphragm, a commercial PP diaphragm and a PE / PP composite diaphragm.
[0043] The method for preparing the multifunctional coated diaphragm for lithium metal battery comprises the following steps: The amide fiber, the binder, the conductive agent, the additive and the solvent are uniformly mixed to obtain a first coating slurry; uniformly mixing the metal compound, the binder and the solvent to obtain a second coating slurry; The first coating slurry is coated on the surface of the base diaphragm 1 by electrostatic spinning, and the first coating layer 2 can be obtained after drying; the second coating slurry is coated on the side of the first coating layer 2 away from the base diaphragm 1 by electrostatic spraying, and the second coating layer 3 can be obtained after drying, thereby obtaining the multifunctional coated diaphragm for lithium metal batteries.
[0044] The first coating slurry includes the following raw materials in percentage by weight: 22-32% of amide fiber, 1-5% of binder, 0-1% of conductive agent, 0-2% of auxiliary agent, and 60-77% of solvent.
[0045] The second coating slurry includes the following raw materials in percentage by mass: 26% of metal compound, 2% of binder, and 72% of solvent.
[0046] The amide fiber is at least one of aramid fiber, polyamide fiber, polyesteramide fiber, polyimide fiber, polysulfoneamide fiber, polyaramid fiber, polynicotineamide fiber, polycarbonamide fiber, polyoxamide fiber, polyoxamide fiber, polyfuranamide fiber, polyfluoroamide fiber, and polyphenylamide fiber; the amide fiber includes the following structure:
[0047] Among them, R 1 and R 2 Same or different, R 1 and R 2 Each of them is independently selected from any one of hydrogen, alkane, alkene, halogenated hydrocarbon, methoxy, benzene ring, oxygen-containing benzene ring, acyl, halogenated acyl, benzoyl, amide, and halogen elements.
[0048] The metal compound is at least one of metal oxides, metal sulfides, metal selenides, metal phosphides, metal nitrides and metal fluorides.
[0049] The binder is at least one of polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyacrylic acid, polyethylene oxide, sodium carboxymethyl cellulose, styrene butadiene rubber, hydroxypropyl methylcellulose, carboxy styrene butadiene latex and polyvinyl alcohol.
[0050] The auxiliary agent is at least one of perfluoroalkyl ethoxymethyl ether, lithium polyacrylate, polyoxyethylene alkylamide, lithium chloride, fatty alcohol polyoxyethylene ether, sodium butylnaphthalene sulfonate, sodium isethionate, polyvinylidene fluoride-hexafluoropropylene, silicon dioxide, sodium dodecyl sulfonate, polyethylene oxide, polysiloxane, and carboxymethyl cellulose salt.
[0051] The conductive agent is one or more of carbon black, conductive graphite, carbon fiber, carbon nanotube, and graphene.
[0052] The solvent is one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, potassium hydroxide solution, acetonitrile, ethanol, isopropanol, tert-butanol, ethylene glycol dimethyl ether, dimethyl sulfoxide, and deionized water.
[0053] The electrospinning voltage is 22 kV, the distance between the roller and the needle is 10-20 cm, and the needle advancement speed is 0.2-1 mL / h.
[0054] The electrostatic spray voltage is 10 kV, the spraying distance is 10-20 cm, and the needle advancement speed is 0.5-2 mL / min.
[0055] Example 1
[0056] A multifunctional coated separator for lithium metal batteries, having a structure such as Figure 1 As shown, the preparation method is as follows: 25g of polyisophthalamide fiber, 2g of lithium chloride, 2g of polyvinylidene fluoride and 1g of graphene are added to 70g of N,N-dimethylacetamide, mixed and stirred evenly to prepare a first coating slurry, and the first coating slurry is coated on one side of the base diaphragm 1 by electrostatic spinning as the first coating layer 2; the electrospinning voltage is 22kV, the distance between the roller and the needle is 15cm, the needle advancement speed is 0.5mL / h, and the thickness of the first coating layer 2 is 3μm; then 13g of nano-alumina and 1g of polyvinylidene fluoride are added to 36g of N-methylpyrrolidone to form a second coating slurry, and the second coating slurry is coated on the side of the first coating layer 2 away from the base diaphragm 1 by electrostatic spraying, and the second coating layer 3 is obtained after drying, the electrostatic spray voltage is 10kV, the spraying distance is 15cm, the needle advancement speed is 1mL / min, and the thickness of the second coating layer is 3μm, to obtain a multifunctional coated diaphragm for lithium metal batteries, and the base diaphragm 1 is a PE diaphragm.
[0057] Example 2
[0058] A multifunctional coated diaphragm for lithium metal battery, the preparation method of which is as follows: 25g of polyterephthalamide fiber and 2g of lithium chloride were mixed and stirred evenly in 60g of dimethyl sulfoxide and 13g of 50% by mass potassium hydroxide solution to prepare a first coating slurry, and the first coating slurry was coated on one side of the base diaphragm 1 by electrospinning as the first coating layer 2; the thickness of the first coating layer 2 was 3μm; the electrospinning voltage was 22 kV, the distance between the roller and the needle was 10cm, and the needle advancement speed was 0.2mL / h. Then, 13g of nano-alumina and 1g of polyvinylidene fluoride were added to 36g of N-methylpyrrolidone to form a second coating slurry, and the second coating slurry was coated on the side of the first coating layer 2 away from the base diaphragm 1 by electrostatic spraying. After drying, the second coating layer 3 was obtained. The electrostatic spray parameters were set to a voltage of 10 kV, a spraying distance of 10cm, a needle advancement speed of 0.5mL / min, and a second coating layer thickness of 3μm, to obtain a multifunctional coated diaphragm for lithium metal batteries, and the base diaphragm 1 was a PE diaphragm.
[0059] Example 3
[0060] A multifunctional coated diaphragm for lithium metal battery, the preparation method of which is as follows: 12.5g of polyimide fiber, 1g of lithium chloride, 1g of polyvinylidene fluoride and 35.5g of acetonitrile were mixed and stirred evenly to prepare a first coating slurry, and the first coating slurry was coated on one side of the basic diaphragm 1 by electrostatic spinning as the first coating layer 2; the thickness of the first coating layer 2 was 3μm; the electrostatic spinning parameters were set to a voltage of 22kV, a distance between the roller and the needle of 10cm, and a needle advancement speed of 1mL / h. Then, 13g of nano-alumina and 1g of polyvinylidene fluoride were added to 36g of N-methylpyrrolidone to form a second coating slurry, and the second coating slurry was coated on the side of the first coating layer 2 away from the basic diaphragm 1 by electrostatic spraying. After drying, a second coating layer 3 was obtained. The electrostatic spray parameters were set to a voltage of 10kV, a spraying distance of 20cm, a needle advancement speed of 12mL / min, and a second coating layer thickness of 3μm, to obtain a multifunctional coated diaphragm for a lithium metal battery, and the basic diaphragm 1 was a PE diaphragm.
[0061] Example 4
[0062] A multifunctional coated separator for lithium metal batteries, which is the same as the preparation process of embodiment 1, except that the same mass of SnS is used. 2 Nano flakes replace nano alumina.
[0063] Example 5
[0064] A multifunctional coated diaphragm for lithium metal batteries has the same preparation process as that of implementation 1, except that an equal mass of sodium carboxymethyl cellulose is used to replace polyvinylidene fluoride.
[0065] Comparative Example 1 A multifunctional coated diaphragm for lithium metal batteries, compared with embodiment 1, the difference is that the first coating slurry is coated on both sides of the PE diaphragm to form a coating layer, the coating layer thickness is 3um, and the preparation process of the first coating slurry and the coating process are the same as embodiment 1.
[0066] Comparative Example 2 A multifunctional coated diaphragm for lithium metal batteries, compared with embodiment 1, the difference is that the second coating slurry is coated on both sides of the PE diaphragm to form a coating layer, the coating layer thickness is 3um, and the second coating slurry preparation process and coating process are the same as embodiment 1.
[0067] Comparative Example 3 A multifunctional coated diaphragm for lithium metal battery, the preparation method of which is as follows: 25g of polyisophthalamide fiber, 2g of lithium chloride, 2g of polyvinylidene fluoride and 1g of graphene are added to 70g of N,N-dimethylacetamide, mixed and stirred evenly to prepare a first coating slurry, and the first coating slurry is coated on one side of the base diaphragm 1 by electrostatic spinning as the first coating layer 2; the electrospinning voltage is 22kV, the distance between the roller and the needle is 15cm, the needle advancement speed is 0.5mL / h, and the thickness of the first coating layer 2 is 3μm; then 13g of nano-alumina and 1g of polyvinylidene fluoride are added to 36g of N-methylpyrrolidone to form a second coating slurry, and the second coating slurry is coated on the side of the base diaphragm 1 away from the first coating layer 2 by electrostatic spraying, and the second coating layer 3 is obtained after drying, the electrostatic spray voltage is 10kV, the spraying distance is 15cm, the needle advancement speed is 1mL / min, and the thickness of the second coating layer is 3μm, to obtain a multifunctional coated diaphragm for lithium metal batteries, and the base diaphragm 1 is a PE diaphragm.
[0068] Comparative Example 4 This comparative example is a commercial PE diaphragm.
[0069] Comparative Example 5 This comparative example is a commercial PP diaphragm assembly.
[0070] Comparative Example 6 This comparative example is a commercial three-layer composite ceramic diaphragm.
[0071] Comparative Example 7 This comparative example is a commercial PI diaphragm.
[0072] Comparative Example 8 This comparative example is a commercial PE / PP composite diaphragm.
[0073] Test example The separators in Examples 1-5 and Comparative Examples 1-8 were assembled into Li||NMC811 full batteries, and the specific method was as follows: The positive electrode material is commercial LiNi 0.8 Co 0.1 Mn 0.102, punched out into 10mm diameter discs with a punching machine; the negative electrode material is a 200μm thick metal lithium foil, which is punched out into 10mm diameter discs with a punching machine; the electrolyte uses a commercial carbonate electrolyte (1M LiPF6 / EC+DEC), and the electrolyte content is 80μl; the diaphragms are respectively selected from the diaphragms made in Examples 1-5 and Comparative Examples 1-8. The button battery is assembled in a glove box with a high-purity argon protective atmosphere (the water and oxygen content is less than 0.1ppm). The assembly order is the negative electrode shell, the pole piece, the lithium battery diaphragm, the electrolyte, the lithium sheet, the gasket, the shrapnel, and the positive electrode shell. The battery is then sealed with a sealing machine to prepare the Li||NMC811 full battery, which is left to stand for 12h for electrochemical performance testing. (Note, during the assembly process of the diaphragms in Examples 1-5, the second coating layer 3 is close to the negative electrode material).
[0074] The lithium metal batteries corresponding to Examples 1-5 and Comparative Examples 1-8 were subjected to room temperature formation and room temperature cycle tests, respectively. The test results are shown in Table 1: Table 1 Lithium metal battery performance test results
[0075] It can be seen from the data recorded in Table 1 that, compared with Comparative Examples 1-8, the lithium metal battery obtained in Examples 1-5 has better electrochemical performance.
[0076] The AC impedance test was performed using a CHO660E electrochemical workstation with a frequency range of 0.01 Hz to 1 MHz. The impedance test was performed on the lithium metal batteries corresponding to the diaphragms of Examples 1-5 and Comparative Examples 1-8 at 20 and 50 cycles. The test results are shown in Table 2: Table 2
[0077] It can be seen from the data recorded in Table 2 that, compared with Comparative Examples 1-8, the lithium batteries corresponding to the separators of Examples 1-5 have better ionic conductivity and lower interface impedance.
[0078] The contact angles of the prepared diaphragms of Examples 1-5 and Comparative Examples 4-8 to the electrolyte were tested using a JC2000D1 contact angle tester. The horizontal axes 1-5 represent Examples 1-5, and the horizontal axes 6-10 represent Comparative Examples 4-8. The contact angles are compared with the ionic conductivity test results. Figure 2 As shown. Figure 2 It can be seen that compared with Comparative Examples 4-8, the diaphragms prepared in Examples 1-5 have lower contact angles and higher ionic conductivity, indicating that the contact performance between the diaphragms prepared in the present invention and the electrolyte is better.
[0079] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0080] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A multifunctional coated diaphragm for lithium metal batteries, characterized in that: comprising a base membrane, a first coating layer and a second coating layer; The first coating layer is disposed on the surface of the base diaphragm, and the first coating layer is an amide fiber coating; The second coating layer is arranged on the surface of the first coating layer, and the second coating layer is a metal compound coating.
2. A multifunctional coated separator for lithium metal batteries according to claim 1, characterized in that: The first coating layer is made of a first coating slurry, which includes the following raw materials in percentage by mass: 22-32% of amide fiber, 1-5% of a binder, 0-1% of a conductive agent, 0-2% of an additive, and 60-77% of a solvent.
3. A multifunctional coated separator for lithium metal batteries according to claim 1 or 2, characterized in that: The second coating layer is made of a second coating slurry, and the second coating slurry includes the following raw materials in percentage by mass: 26% of metal compound, 2% of binder, and 72% of solvent.
4. The multifunctional coated separator for lithium metal battery according to claim 2, characterized in that: The amide fiber comprises the following structure: ; Among them, R1 and R2 are the same or different, and R1 and R2 are independently selected from any one of hydrogen, alkane, alkene, halogenated hydrocarbon, methoxy, benzene ring, oxygen-containing benzene ring, acyl, halogenated acyl, benzoyl, amide, and halogen elements.
5. A multifunctional coated separator for lithium metal batteries according to claim 4, characterized in that: The amide fiber is at least one of aramid fiber, polyamide fiber, polyesteramide fiber, polyimide fiber, polysulfoneamide fiber, polyaramid fiber, polynicotineamide fiber, polycarbonamide fiber, polyoxamide fiber, polyoxamide fiber, polyfuramide fiber, polyfluoroamide fiber, and polyphenylamide fiber.
6. The multifunctional coated separator for lithium metal battery according to claim 3, characterized in that: The metal compound is at least one of metal oxide, metal sulfide, metal selenide, metal phosphide, metal nitride and metal fluoride.
7. The multifunctional coated separator for lithium metal battery according to claim 1, characterized in that: The thickness of the basic diaphragm is 5-16um; And / or the thickness of the first coating layer is 3-5um; And / or the second coating layer has a thickness of 3-5 μm.
8. A method for preparing a multifunctional coated diaphragm for a lithium metal battery according to any one of claims 3 to 6, characterized in that: The following steps are involved: Mixing amide fiber, a binder, a conductive agent, an additive and a solvent to obtain a first coating slurry; Mixing a metal compound, a binder, and a solvent to obtain a second coating slurry; Applying the first coating slurry to the surface of the base diaphragm by electrospinning, and obtaining a first coating layer after drying; The second coating slurry is coated on the side of the first coating layer away from the base diaphragm by electrostatic spraying, and the second coating layer can be obtained after drying, that is, the multifunctional coated diaphragm for lithium metal battery is obtained.
9. The method for preparing a multifunctional coated diaphragm for a lithium metal battery according to claim 8, characterized in that: The electrospinning voltage is 22 kV, the distance between the roller and the needle is 10-20 cm, the needle advancement speed is 0.2-1 mL / h, the electrostatic spraying voltage is 10 kV, the spraying distance is 10-20 cm, and the needle advancement speed is 0.5-2 mL / min.
10. A lithium metal battery comprising a separator, characterized in that: The separator is the multifunctional coated separator for lithium metal battery according to any one of claims 1 to 7.
Citation Information
Patent Citations
Polysulfone amide / titanium dioxide / polysulfone amide composite lithium battery diaphragm and preparation method thereof
CN108819393A
Conductive coating, coating method and application
CN112864398A
Triazinyl conjugated microporous polymer / carbon nanotube composite material, composite lithium-sulfur battery diaphragm as well as preparation method and application of composite lithium-sulfur battery diaphragm
CN115275515A
Composite coating diaphragm and preparation method thereof
CN115863920A
Ceramic coating diaphragm, preparation method thereof and secondary battery
CN118712657A